2018
DOI: 10.1371/journal.pone.0204097
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of imidacloprid on the performance of the bird cherry-oat aphid Rhopalosiphum padi

Abstract: The bird cherry-oat aphid, Rhopalosiphum padi (L.), is a major insect pest of cereal crops in many countries. Imidacloprid has been widely used for controlling piercing-sucking insect pests worldwide, but its sublethal effects on R. padi have not been well addressed. In this study, we investigated the sublethal effects of imidacloprid on biological parameters and five enzyme activities of R. padi. The LC10, LC20, and LC25 of imidacloprid to adult aphids were 0.0053, 0.0329 and 0.0659 mg L-1, respectively. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…This suggests the gene plays an essential role in stress defense. A similar increase in Cat expression in response to under these environmental stresses was also observed in other insect species, including Rhopalosiphum padi, Frankliniella occidentalis, Xylotrechus rusticus, C. suppressalis , and Heortia vitessoides (Cheng et al, 2018; Ding et al, 2015; W. Li et al, 2018; Lu et al, 2017; Qin et al, 2017; Xu et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…This suggests the gene plays an essential role in stress defense. A similar increase in Cat expression in response to under these environmental stresses was also observed in other insect species, including Rhopalosiphum padi, Frankliniella occidentalis, Xylotrechus rusticus, C. suppressalis , and Heortia vitessoides (Cheng et al, 2018; Ding et al, 2015; W. Li et al, 2018; Lu et al, 2017; Qin et al, 2017; Xu et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…Compensatory effects might exist in A. lucorum to synchronize the developmental rate of various populations. Similarly, Li et al 43 observed a longer oviposition period in R. padi treated by imidacloprid, while a shorter oviposition period was documented in A. lucorum 18,41 and A. glycines 42 . Additionally, imidacloprid significantly extended the nymphal development duration of M. persicae 17,23 and R. padi 43 .…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, Li et al 43 observed a longer oviposition period in R. padi treated by imidacloprid, while a shorter oviposition period was documented in A. lucorum 18,41 and A. glycines 42 . Additionally, imidacloprid significantly extended the nymphal development duration of M. persicae 17,23 and R. padi 43 . In contrast, a reduction in nymphal development duration was reported in A. lucorum 41 , B. tabaci 15 , A. gossypii 24,34 , and A. glycines 42 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The age-stage, two-sex life table and EPGs are two useful tools to assess the population-level performance and feeding behaviour of insects [26][27][28][29]. This kind of life table approach considers both sexes and stage differentiation and can estimate population parameters more accurately than the traditional female age-specific life tables [29,30].…”
Section: Introductionmentioning
confidence: 99%